Plausible deniability: Integration vs. outsourcing with heterogeneous firms and unethical suppliers - Claudius Löhnert (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2022)
This paper presents a property rights model of the international organization of production, where heterogeneous headquarter firms source from suppliers in the Global South. Due to weak regulatory stringency in the Global South, suppliers can employ a cost-saving technology. Consumers, however, consider this technology as unethical and may therefore participate in a consumer boycott, if they consider a firm to be responsible for its supplier's conduct. The paper analyzes how the international organization of production and the choice of technology interact with each other as well as sectoral characteristics. It identifies three mechanisms that govern whether integration is preferred by high-productivity firms in a given sector: the Antràs mechanism (severity of underinvestment by headquarter vs. supplier), the unethical mechanism (cost savings vs. boycott risk) and the deniability mechanism (higher boycott risk under integration than under outsourcing). The equilibrium share of active firms who integrate in a sector increases with productivity dispersion and decreases in the sector's cost advantage of unethical production.
Keywords: D23; F12; F23; F61; L11; L23; L31; O35; 330; international outsourcing; property rights theory; heterogeneousfirms; ethical production; consumer boycotts; NGOs; social activism